Existential Humanistic Paradigm in Girish Karnad's ''Hayavadana'' (Global Journal of Human-Social Science, 2019)
This paper attempts to interrogate Girish Karnad's 'Hayavadana' from the perspective of existentialism relating the protagonist to main concerns of existential paradigm such as freedom, choice, responsibility, finitude and death. Individual's variety of responses to fear and anxieties forge a paradoxical identity which tries to avert the inevitability through human efforts and subverts the symbolic identity, to seek meaning in interpersonal relationship and life. Hayavadana engages with this dual reality of human being which Becker refers to "existential paradox". The way an individual conflates this paradox, has been analysed from the existential human paradigms which involves inner experiences, desires, memories and the sense of alienation. It further investigates the societal myth of an individual used by Karnad to locate a man in the larger human context. It further argues that Karnad poses a problem of identity in a world of tangled relationship.
Keywords: existentialism; paradoxical identity; paradigms; alienation; futility